Synthesis of Nano-Sized Cobalt oxide Nano-Particles Stabilized in Surfactant and Polymer Matrix and their Magnetic Properties - Fadi Mohammad Mostafa Naalweh (My University, 2013)
In this work, different-sized cobalt oxide nano- rods were selectively synthesized with narrow size distribution, by using chemical preparation methods, which could be carried out by the salt reduction technique. The samples were prepared at different temperatures, and two different types of stabilizer PVP and TOAB were added. Smaller sizes of the samples were obtained in the presence of stabilizer, and the type of stabilizer had no effect on the size. The size of the samples increased with increasing the temperature at which the synthesis of the nanoparticles was performed. The magnetic measurements showed that the nano-rods had a superparamagnetic and paramagnetic character, which depended on the size of the samples and on the existence of the stabilizer. The type of stabilizer had affected the magnetic property of the samples. The superparamagnetic component of the sample that was prepared with Polyvinyl-pyrrolidone (PVP) stabilizer was stronger than that prepared with Tetraoctylammonium bromide (TOAB) stabilizer.

في هذه الدراسة تم تحضير عينات مختلفة الحجم من أكاسيد الكوبالت باستخدام طرق كيميائية حيث تم استخدام طريقة اختزال الملح, على درجات حرارة مختلفة وبإضافة نوعين مختلفين من أنواع المثبت PVP و TOAB. وجد أن العينات التي كانت تحتوي على مثبت كان حجمها صغير في حجم النانو, بينما التي كانت لا تحتوي على مثبت كانت في حجم الميكرو. نوع المثبت المستخدم لم يكن له تأثير على الحجم. وتبين كذلك من هذه الدراسة أن درجة الحرارة المستخدمة أثناء التحضير تؤثر على الحجم, حيث أن الحجم يزداد بزيادة تلك الدرجة. العينات التي لا تحتوي على أي نوع من المثبت أظهرت النتائج أنها عبارة عن paramagnrtic, والعينات التي تحتوي على المثبت بنوعيه ذات الحجم النانوني عبارة عن paramagnetic with superparamagnetic. الخصائص المغناطيسية تتأثر بنوعية المثبت, حيث أن المثبت من نوع PVP كانت فيه superparamagnetic component أقوى من المثبت من نوع TOAB.
تحضير عينات من أكاسيد الكوبالت على شكل جزيئات نانونية ودراسة خصائصها المغناطيسية